Biological Dynamics of Forest Fragments Bibliography - Tovah Siegel; Jesse Wong; Wendy Mann; Dr. José Luís Camargo; Dr. Thomas E. Lovejoy; Dr. David Luther (Open Science Framework, 2022)
Coordinated by the Instituto Nacional de Pesquisas da Amazônia, the Biological Dynamics of Forest Fragments Project (BDFFP) is the longest-running and largest experimental habitat fragmentation site in the world. The Bibliography lists peer-reviewed papers that have resulted from BDFFP research. A new list of publications is generated annually.